Problem Based Learning (PBL) - Problem Solving Skills (PSS): Systematic Literature Review - Hudha, Muhammad Nur; Etikamurni, Daniar Pangastiningasih; Rasuli, Intan Permatasari Ayunda; Safitri, Nur Shabrina; Perwita, Cholisina Anik; Ayu, Hena Dian (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
At this time, education in Indonesia has entered the 21st century, which requires students to have 21st century skills, one of which is problem-solving skills (PSS). PSS is needed in life so that students can solve their problems appropriately, effectively, and efficiently. One way to increase students' PSS is to use varied and innovative learning models, such as problem-based learning (PBL). This research is an SLR study that aims to find out whether PBL can affect the increase in student PSS. The methodology in this study included identifying objectives by creating research questions, drafting implementation for the writing team, screening inclusion, searching for literature/ references, taking the essence of selected articles, screening exclusions, conducting synthesis, and writing studies. This study used one database, namely SCOPUS, with a total of 167 articles in the time period from 2013 – 2022. Then, these 167 articles were filtered by inclusion and exclusion so that 69 articles were obtained that were worthy of review. The results of the review of 69 articles can be presented as follows: (1) Indonesia is the country that has conducted the most research on the effect of PBL on PSS; (2) The fields of study involved in this research are very varied, but mathematics and health dominate the most; (3) The research objects involved also vary with the level of student education that dominates; (4) The general result of this study is that PBL can increase students' PSS, although there are several studies that contradict these results; (5) The learning model used is PBL, which has been combined with other learning models that are more innovative and creative. The conclusion of this study is that PBL can increase students' PSS.